POPULATION DYNAMICS AND VARIETAL SCREENING OF OKRA AGAINST TETRANYCHUS MACFARLANEI (BAKER AND PRITCHARD) - KUMAR, KETAN; PATEL, M.B.; SHUKLA, ABHISHEK; KUMAR, KAPIL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Field experiment was conducted during kharif-2008 at N.M. College of Agriculture, Naysari Agricultural University, Naysari on okra cultivars Parbhani Kranti, Arka Anamika, Pusa Sawani, Go-2 and LSVT (AOL-03-1) to screen for resistance to mite (Tetranychus macfarlanei), the cultivar LSVT (AOL-03-1), GO-2 and Arka Anamika supported lowest population of mite and proved to be resistant. The highest population of mite was observed in Parbhani Kranti and found to be highly susceptible. Among various weather parameters studied temperature, relative humidity, sunshine hours, rainy days and evaporation had positive influence on the population of mite whereas, rain fall and wind velocity had marked negative effect.